Surgical Management of Diaphragmatic Hernia in a Dog - Gaikwad, Shahir V; Khandekar, Gajendra S.; Tripathi, Santoshmani D; Rohi, Rajesh R; Rani, Monika (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Diaphragmatic hernia is a serious condition with a high mortality rate, characterized by the passage of  abdominal organs into the thoracic cavity due to tear in the  diaphragm. This condition, often resulting from trauma,  leads to significant clinical symptoms (Ozer et al., 2007;  Radlinsky and Fossum, 2013; Park and Lee, 2018; Yaygıngul  et al., 2019; Zamirbekova et al., 2020). The diaphragm, which  has a musculotendinous structure, is more robust at its  center compared to its peripheral areas. Consequently,  most abnormal openings occur where the diaphragm  attaches to the ribs (Zamirbekova et al., 2020). In cats and  dogs, diaphragmatic hernias result from congenital (5-10%)  and traumatic (85%) causes, while 10-15% of cases have  unknown origins (Radlinsky and Fossum, 2013; Park and  Lee, 2018; Zamirbekova et al., 2020). A definitive diagnosis of  diaphragmatic hernia requires radiography. Key radiographic  indicators include the absence of the diaphragm line, a  silhouetted appearance of the heart, lung displacement,  and the presence of abdominal organs and gas within the  chest cavity (Burns et al., 2013; Nikiphorou et al., 2016; Ozer  et al., 2007). Surgical intervention is the sole treatment for  diaphragmatic hernias (Park and Lee, 2018; Yaygıngul et al.,  2019). This study details the diagnosis and successful surgical  management of a traumatic diaphragmatic hernia in a 3-year old stray dog.
Keywords: diaphragm; Yaygıngul